Pengaruh Konsentrasi Dekstrin dan Tween 80 (Polyoxyethylene Sorbitan Monooleat) pada Proses Pengeringan Gel Daun Lidah Buaya (Aloe barbadensis Miller) dengan Cabinet Dryer. - Saputra, I Wayan Adi; Pudja, I.A Rina Pratiwi; Gunadnya, I.B.P (Jurnal BETA (Biosistem dan Teknik Pertanian); Vol 4 No 2 (2016): September, 2016)
This study was conducted to determine the effect of the concentration of dextrin and tween 80 in the drying process by using dryer cabinet and determine the concentration of dextrin and tween 80 which can speed up the drying process of aloe vera gel. This study used a Randomized Complete Design (RBD) with 2 factors. The first factor was the concentration of dextrin (10%, 14%, 18%, 22%) and the second factor was the concentration of tween 80 (0.3%, 0.4%, 0.5%) with the drying temperature of 70°C. The experiment was repeated three times. Observations were made every 2 hours until the sample weight did not decrease. Variables which observed were rate of drying, whiteness, yield, and pH of flour aloe vera. The results showed that concentrations of dextrin and tween 80 significantly affected water content, the degree of whiteness of the flour was affected by concentrations of dextrin. Treatment interaction between dextrin concentration and tween 80 did not significantly affect all parameters observed. The addition of dextrin will slow the drying process, on the contrary the addition of tween 80 will speed up the drying process. The highest yield at amount of 10.99% was obtained from the treatment interaction of 22% dextrin with 0.3% tween 80. The degree of acidity (pH) of the flour at 4.00 which was the highest value of pH was yielded form the treatment interaction of 10% dextrin with 0.5% tween 80. In this study, the best treatment resulting aloe vera flour that approaching the standards of quality of Terry Laboratories was a treatment interaction of 22% dextrin with 0.3% tween 80. The flour had a water content of 8.68%, the degree of whiteness 50.51, yield 10.99%, and the degree of acidity (pH) 3.65.
Keywords: aloe vera flour; dextrin; tween 80; cabiner drayer